As recentes tendências no mercado imobiliário costarriquenho - Acosta Schnell, Sabrine (2015)
San Jose, Costa Rica is undergoing significant changes related to the technical innovation in the area of construction, changes in legislation and the imposition of a new way of living. The intensification of urbanization led to the fast residential verticalization in strategic points of the Gran Área Metropolitana. This article presents the recent trends in the housing market, highlighting key factors that contribute and limit the local real estate development. It is also analysed the different agents and financing methods involved in the housing sector. It is discussed the differences between use value and exchange value of these recent residential projects and how location influences this differences.